Produksi Film PSA â€œKita Indonesiaâ€ Sebagai Media Komunikasi Berbasis Multimedia - Tsabiet, Muhammad; Supriyadi, Supriyadi (Jurnal Komunikasi, 2018)
Film is one powerful tool in the hands of people who use it effectively for a purpose, especially for the general public as well as children who do use more emotional aspects than their rational aspects, and immediately speak to the hearts of the audience convincingly. Films are also very helpful in the learning process, what is respected by the eyes and heard by the ears, faster and easier to remember than what can only be read or only heard. AKOM BSI Jakarta Program Study Â Broadcasting develops its expertise to try to penetrate the film world through multimedia technology. In collaboration with the Ministry of Home Affairs (Kemendagri) during the "Pekan Kerja Nyata Revolusi Mental", this PSA film "Aku Indonesia" was used as an information media to the public, which later became a commercial film right on target for the audience. The film produces a quality and quality video in delivering messages that are right on target at this time. The benefits of this research are to provide creative and varied film breakthroughs in order to improve the nation's intellectuality, as well as increase the repertoire of film library. The research method used is Literature, Observation, Interview, Design and Implementation, Documentation. The formulation of cinema production steps consists of the process of Pre Production, Production and Post Production.The implementation of this film production is expected to be a reference and information in producing quality according to the rules of the world of cinematography and multimedia systems.Keywords: Sinematografi, PSA, Insctrutional, Media